Etomidate and the Risk of Complications After Cardiac Surgery: A Retrospective Cohort Analysis. Issue 2 (April 2017) - Komatsu, R.; Makarova, N.; You, J.; Sessler, D. I.; Anthony, D. G.; Kasuya, Y.; Soltesz, E. G.; Turan, A.
Abstract : (Abstracted from J Cardiothorac Vasc Anesth, 30(6):516–1522, 2016) The primary aim of this retrospective cohort study was to compare the incidence of atrial arrhythmia, duration of care, and major complications in cardiac surgery patients who received etomidate and those who received other induction agents.